2014
DOI: 10.1112/s0010437x14007544
|View full text |Cite
|
Sign up to set email alerts
|

The diminished base locus is not always closed

Abstract: We exhibit a pseudoeffective R-divisor D_\lambda on the blow-up of P^3 at nine very general points which lies in the closed movable cone and has negative intersections with a set of curves whose union is Zariski dense. It follows that the diminished base locus B_-(D_\lambda) = \bigcup_{A ample}} B(D_\lambda+A) is not closed and that D_\lambda does not admit a Zariski decomposition in even a very weak sense. By a similar method, we construct an R-divisor on the family of blow-ups of P^2 at ten distinct points, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…Fix an ample line bundle A and a rational number ε > 0. We define Furthermore, as we mentioned earlier, Lesieutre [13] proved that there exist line bundles which are pseudo-effective but not weakly positive. In particular, B − (L) is not necessarily closed.…”
Section: Positivity Properties For Line Bundlesmentioning
confidence: 94%
“…Fix an ample line bundle A and a rational number ε > 0. We define Furthermore, as we mentioned earlier, Lesieutre [13] proved that there exist line bundles which are pseudo-effective but not weakly positive. In particular, B − (L) is not necessarily closed.…”
Section: Positivity Properties For Line Bundlesmentioning
confidence: 94%
“…7] gave an example of such behavior in characteristic p>0. Lesieutre [, Thm. 1.2] showed that this is also possible over the complex numbers if one allows double-struckR‐divisors instead of line bundles.…”
Section: Semistability In Familiesmentioning
confidence: 99%
“…Said another way, given the behavior of nefness in families (cf. [10,11]), it is unclear if numerical pull-back can be preserved after reduction to positive characteristic. In a sense, this is the difficulty that must be avoided in proving Theorem 1, as otherwise one could use Proposition 17 in order to verify (3.1).…”
Section: Some Open Questionsmentioning
confidence: 99%